IMPLEMENTATION OF REGIONAL FINANCIAL MANAGEMENT POLICY AT THE DPPPA OF NORTH MINAHASA DISTRICT - Willy Candra Rompies; Jetty E. H. Mokat; Xaverius E. Lobja (Journal of International Islamic Law, Human Right and Public Policy, 2026)
The Women's Empowerment and Child Protection Agency (DPPPA) of North Minahasa Regency recorded budget realization of 84.19% in Fiscal Year 2025 and was in the fifth lowest position of all regional agencies, with three programs recording the lowest realization: the Special Child Protection Program at 70.31%, the Supporting Program at 83.45%, and the Women's Protection Program at 84.69%. Budget absorption as a fundamental dimension in regional financial management makes this condition require further study based on North Minahasa Regency Regulation Number 6 of 2022 concerning Regional Financial Management, particularly on the principles of orderliness and effectiveness, while identifying the factors that influence it. This study used a descriptive qualitative approach with four informants: Acting Head of the Service, Head of the KAG and PKH Division, Planner, and Counselor of the UPTD PPA. Data were collected through in-depth interviews and document review, then analyzed using the Miles and Huberman model with source triangulation and technique triangulation. The results of the study indicate that implementation is not optimal. In terms of orderliness, the aspect of timeliness is met, but the aspect of appropriateness has not been fully met because several budget items cannot be executed according to their objectives, namely SILPA DAK Non Fisik of Rp70,368,650.00 which cannot be disbursed, remaining employee expenditure due to vacant ASN formations, and remaining BOPPA due to the reactive characteristics of the program. In terms of effectiveness, services to 46 victims are running well and confirmed by a satisfaction survey, but the benefits of socialization and prevention activities have not fully reached the wider community. Inhibiting factors include employee vacancies, coordination between agencies, DAK technical capabilities, and the reactive characteristics of the program, while supporting factors include internal employee conditions and service commitment.